2002
DOI: 10.1128/jcm.40.8.2897-2902.2002
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Bacillus anthracis DNA by LightCycler PCR

Abstract: Anthrax is a zoonotic disease that is also well recognized as a potential agent of bioterrorism. Routine culture and biochemical testing methods are useful for the identification of Bacillus anthracis, but a definitive identification may take 24 to 48 h or longer and may require that specimens be referred to another laboratory. Virulent isolates of B. anthracis contain two plasmids (pX01 and pX02) with unique targets that allow the rapid and specific identification of B. anthracis by PCR. We developed a rapid-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
78
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(79 citation statements)
references
References 23 publications
0
78
0
1
Order By: Relevance
“…Polymerase chain reactions (PCR) or multiplication of the microorganism through culture growth are used to generate the millions of copies that are required to accurately sequence the nucleic acid. Although B. anthracis identification by PCR has been demonstrated by sequencing the capsular protein B gene in under 1 h, 3 the CDC required several days to identify the contents of the letter addressed to Senator Tom Daschle as B. anthracis, and longer still to verify that it was the deadly Ames strain. 1 Immunoassay methods are also being developed that use competitive binding of the bioagent (as an antigen) and its labeled conjugate for a limited number of antibodies.…”
Section: Introductionmentioning
confidence: 99%
“…Polymerase chain reactions (PCR) or multiplication of the microorganism through culture growth are used to generate the millions of copies that are required to accurately sequence the nucleic acid. Although B. anthracis identification by PCR has been demonstrated by sequencing the capsular protein B gene in under 1 h, 3 the CDC required several days to identify the contents of the letter addressed to Senator Tom Daschle as B. anthracis, and longer still to verify that it was the deadly Ames strain. 1 Immunoassay methods are also being developed that use competitive binding of the bioagent (as an antigen) and its labeled conjugate for a limited number of antibodies.…”
Section: Introductionmentioning
confidence: 99%
“…Anthrax detection can be performed by amplifying the virulence plasmids (23)(24)(25), but as with Y. pestis, there is concern over genetic modification of near neighbors and false negatives from B. anthracis without one or more of the plasmids. Moreover, B. cereus and Bacillus thuringiensis isolates have been found that harbor 1 or both B. anthracis plasmids with and without anthrax toxin genes (26 -31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Immunoassays, which rely on the interaction between B. anthracis spore surface antigens and their specific antibodies, can detect 10 5 spores in approximately 12 h. However, in the case of immunoassays, specific antibodies and additional molecular fluorophores and/or enzymatic reactions must be employed for the desired agents to be detected, and mobile-phase conditions must also be adjusted depending on their capture, elution, and separation properties. In addition, although this direct spore detection system is relatively fast, the lack of accuracy and limited sensitivity of current antibody-based detection methods result in unacceptably high levels of both false-positive and false-negative responses [12][13][14]. Therefore, the development of a more robust detection system is required.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, label-free methods implemented for the specific detection of DNA strands were developed [10,11]. Among the most important biological methods for the detection of anthrax, Polymerase Chain Reaction (PCR) [5][6][7] and immunoassay [12][13][14] have been used as representatives. PCR, a primer-mediated enzymatic DNA amplification method, requires expensive reagents and takes 3-4 h or longer several hours to obtain the result.…”
Section: Introductionmentioning
confidence: 99%